The Influence of Utilizing Inquiry-Based Learning Strategy on Science Accomplishment of Primary Students’ Stage - Abdellateef Alqawasmi; Najeh Rajeh Alsalhi; Sami Sulieman Al Qatawneh (International Journal of Interactive Mobile Technologies (iJIM), 2024)
This study examines the impact of inquiry-based learning (IBL) on the academic performance of third-grade students in the science unit “Materials” from the third-grade science textbook in schools under the Directorate of Education in Irbid, Jordan. A sample of 71 students was selected and separated into two groups: an experimental group of 36 students and a control group of 35 students. The empirical group used IBL, while the reference group was taught using conventional teaching techniques. An achievement test of multiple-choice questions was prepared for the study, comprising 24 items. The test’s content validity was confirmed through expert judgment, and its reliability was assessed using Cronbach’s alpha coefficient, which was found to be 0.83. The test’s content validity was confirmed through expert judgment, and its reliability was assessed using Cronbach’s alpha coefficient, which was found to be 0.83. Data were collected and processed using SPSS software. The findings showed statistically significant differences in the average scores of the study participants on the post-test based on the teaching technique variable, indicating a preference for survey-based learning. Based on these findings, the investigation recommends providing in-service and pre-service training on IBL for science supervisors and teachers at the primary education level.